The hidden power of struggling; When women at the crossroads between nature and culture - Susamto, Dina Amalia; Mujiningsih, Erlis Nur; Purwaningsih, Purwaningsih; Susilastri, Dian (Wacana, Journal of the Humanities of Indonesia, 2023)
Women and nature have a bonding which reflect the connectedness between humans and non-humans. The exploitation of women affects nature and vice-versa. The novels Entrok, written by Okky Madasari, Tarian Bumi by Oka Rusmini, and Trilogi Ronggeng Dukuh Paruk by Ahmad Tohari narrate the experiences of women struggling to survive in cultures dominated by the patriarchal system. This article uses qualitative research methods to describe data about the women’s experiences of their encounters with exploitation in these three novels. All data were decoded using the ecofeminism theory. The results show that their nurturing character is a power in the spirituality of women, and it was used in patriarchal systems. The notion of feminization, which preserves both nurture and love, proved insufficient for this purpose as it objectifies women and weakens the struggle. To strengthen the advancement of women, it is important to develop the ethical relationship between humans and nature.